The changing meaning of Taylagan Festival for contemporary Russia Buryat society: An adaptation of tradition - Rania Ayu Shila Febriani Adari; Mina Elfira (SIMULACRA: JURNAL SOSIOLOGI, 2021)
Festival is a product of a culture that develops according to the needs and times, including the Taylagan Festival. Taylagan Festival is one of the most important annual rituals for the Russian Buryat Shamans. In the contemporary era, this festival has also been performed for tourists. By using Roland Barthes’s semiotic theory, this research explores the impact of the changes of Taylagan Festival meanings for Russian Buryat contemporary society. At the same time, Eric Hobsbawm’s “The Invention of Tradition" (1992) is used to investigate the inventory of Taylagan Festival traditions, based on qualitative data collected through intensive interviews for selected informants. By using the descriptive analysis method, the research result shows that the change in the sacred values of the Russian Buryat Shamans in the Taylagan Festival has been started since the presence of Neo-shamans as a form of cultural adaptation during the Contemporary Era, which is known to be more modern and active in social and cultural activities.